Designing a Copywriting E-Booklet to Promote Palembang Culinary Tourism in 26 Ilir Area - Rizky Aliansyah; Koryati; Achmad Leofaragusta K.K. (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2026)
ABSTRACT: This research aims to design a culinary tourism e-booklet using the AIDA (Attention, Interest, Desire, Action) copywriting model to promote culinary tourism in 26 Ilir Area, Palembang. The main issue identified was the absence of practical and engaging digital media to help tourists easily discover recommended traditional foods in the area. The study applied the Research and Development (RnD) method using the ADDIE model, which included four stages: analysis, design, development, and implementation, while evaluation was not included due to the writers’ limitations. The data were collected through observations, documentation, and interviews with experts in the fields of copywriting, English language, and graphic design. The results showed that the integration of AIDA-based copywriting E-booklet by using analysis, design, development, and implementation stages as part of the ADDIE model was judged valid and feasible by expert validators after revision. The developed e-booklet was designed in a digital format, making it accessible across various devices and supporting the promotional efforts of the 26 Ilir Area. Keywords: AIDA model, culinary tourism, copywriting, e-booklet, 26 Ilir Area